Low-Complexity Robotic Device for Magnetic Resonance Imaging-Guided Needle Biopsy - Antoniou, Anastasia; Evripidou, Nikolas; Georgiou, Leonidas; Chrysanthou, Antreas; Christofi, Antonis; Zhao, Jufeng; Yu, Liyang; Li, Wenjun; Damianou, Christakis A. (My University, 2025)
This work presents a low-complexity robotic device for needle-to-target alignment designed to streamline Magnetic Resonance Imaging (MRI)-guided biopsy procedures while maintaining physician control over insertion.
Keywords: MRI; abdominal; agar phantom; biopsy; robotic device